Quantification of rat kisspeptin using a novel radioimmunoassay. - James S Kinsey-Jones; Kylie E Beale; Joy Cuenco; Xiao Feng Li; Stephen R Bloom; Kevin T O'Byrne; Kevin G Murphy (PLoS ONE)
Kisspeptin is a hypothalamic peptide hormone that plays a pivotal role in pubertal onset and reproductive function. Previous studies have examined hypothalamic kisspeptin mRNA expression, either through in situ hybridisation or real-time RT-PCR, as a means quantifying kisspeptin gene expression. However, mRNA expression levels are not always reflected in levels of the translated protein. Kisspeptin-immunoreactivity (IR) has been extensively examined using immunohistochemistry, enabling detection and localisation of kisspeptin perikaya in the arcuate nucleus (ARC) and anteroventral periventricular nucleus (AVPV). However, quantification of kisspeptin-IR remains challenging. We developed a specific rodent radioimmunoassay assay (RIA) capable of detecting and quantifying kisspeptin-IR in rodent tissues. The RIA uses kisspeptin-10 as a standard and radioactive tracer, combined with a commercially available antibody raised to the kisspeptin-10 fragment. Adult female wistar rat brain samples were sectioned at 300 µm and the ARC and AVPV punch micro-dissected. Brain punches were homogenised in extraction buffer and assayed with rodent kisspeptin-RIA. In accord with the pattern of kisspeptin mRNA expression, kisspeptin-IR was detected in both the ARC (47.1±6.2 fmol/punch, mean±SEM n = 15) and AVPV (7.6±1.3 fmol/punch, mean±SEM n = 15). Kisspeptin-IR was also detectable in rat placenta (1.26±0.15 fmol/mg). Reverse phase high pressure liquid chromatography analysis showed that hypothalamic kisspeptin-IR had the same elution profile as a synthetic rodent kisspeptin standard. A specific rodent kisspeptin-RIA will allow accurate quantification of kisspeptin peptide levels within specific tissues in rodent experimental models.